LANGUAGE FUNCTIONS AND MYTH IN FRENCH ADVERTISEMENT - Yulianto, Ahmad (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2015)
Advertisement is a form of communication aimed at attracting consumersâ attention toward a certain product or even influencing the latters to adopt a special behavior. This article views3 advertisements of French Magazine Elle in terms of their referential, emotive, conative, phatic, metalinguistic and poetic functions. Roman JakobsonâsLanguage Functions and Roland Barthesâ Theory of Myth were used to discover the above-mentioned functions. In short, it is important for us to always haveune esprit critique on what we see in the medias since we live in an era of myth and reality. We have to be able to distinguish which is really true and which is false/fake. This type of analysis helps us to unearth what is hidden in any form of communication and bring the truthto the surface.